Clinical and cone beam computed tomography comparison of NovaBone Dental Putty and PerioGlas in the treatment of mandibular Class II furcations - Asmita; Vivek Gupta; Vivek Kumar Bains; G P Singh; Rajesh Jhingran (Wolters Kluwer Medknow Publications, 2014)
Objective: The objective of this study is to compare the putty form of bioactive glass (NovaBone Dental Putty) and particulate form (PerioGlas) in the resolution of Class II furcation defects. Background: Use of bone regeneration materials is becoming common in periodontal surgeries including furcation defects and the promising role of bioactive allograft materials has encouraged their presentation in different morphologic forms with their own advantages and disadvantages giving the operator ample of choices in his/her periodontal armamentarium. Materials and Methods: A total of 28 patients with 40 Class II furcation defects were enrolled in the study and were randomly allocated to two groups with 20 sites in each group. Measurement of defects was done using clinical and cone beam computed tomography (CBCT) methods. The patients were followed-up at 6 months. Intergroup comparisons were done using Mann-Whitney U-test. Results: There was no significance between group differences in clinical parameters and defect size at the baseline. After 6 months, particulate form showed a mean resolution of 50.48 ± 16.47% and 51.11 ± 9.48%, respectively for vertical defect and horizontal defect while putty form showed a mean resolution of 43.48 ± 9.33% and 42.88 ± 11.09%, respectively. Mean resolution in furcation width was 40.15 ± 13.00% for particulate form as compared with 36.27 ± 11.41% in putty form. Statistically, there was no significant difference between two groups except for the horizontal defect fill where PerioGlas showed statistically better results. Conclusion: Putty form was comparable to particulate form for resolution of Class II furcation defects.